Effect of 26 Weeks of Liraglutide Treatment on Coronary Artery Inflammation in Type 2 Diabetes Quantified by [64Cu]Cu-DOTATATE PET/CT: Results from the LIRAFLAME Trial - Jensen, Jacob K.; Zobel, Emilie H.; von Scholten, Bernt J.; Rotbain Curovic, Viktor; Hansen, Tine W.; Rossing, Peter; Kjaer, Andreas; Ripa, Rasmus S. (Frontiers in Endocrinology, 2021)
Background Quantification of coronary artery inflammation and atherosclerosis remains a challenge in high-risk individuals. In this study we sought to investigate if the glucagon like peptide-1 receptor agonist liraglutide has a direct anti-inflammatory effect in the coronary arteries using positron emission tomography (PET) with a radioactive tracer targeting activated macrophages in the vessel-wall. Methods Thirty randomly selected participants with type 2 diabetes from the placebo-controlled trial LIRAFLAME were enrolled in this sub-study. Participants were, prior to enrollment in this sub-study, randomized to either treatment with daily liraglutide (n=15) or placebo (n=15). Both groups underwent a combined [64Cu]Cu-DOTATATE positron emission tomography and computed tomography scan of the heart at baseline and after 26 weeks of treatment. Coronary artery uptake of [64Cu]Cu-DOTATATE were measured as maximum standardized uptake values (SUVmax); and means of the maximum values (mSUVmax), both values were calculated at the level of each participant and each individual coronary-segment. Results SUVmax and mSUVmax values decreased significantly in the liraglutide group both at the participant level (SUVmax: p=0.013; mSUVmax: p=0.004) and at the coronary-segment level (SUVmax: p=0.001; mSUVmax: p<0.0001). No change was observed in the placebo group neither at the participant level (SUVmax: p=0.69; mSUVmax: p=0.67) or at the coronary-segment level (SUVmax: p=0.49; mSUVmax: p=0.30). When comparing the mean change in uptake values between the two groups at both the participant level (SUVmax: p=0.076; mSUVmax: p=0.077) and the coronary segment level (SUVmax: p=0.13; mSUVmax: p=0.11) a borderline significant differences were observed. Baseline SUVmax [64Cu]Cu-DOTATATE uptake values showed a weak positive correlation with the inflammatory biomarker high-sensitivity c-reactive protein (τ =0.26, p=0.045). Conclusion Liraglutide treatment for 26-weeks caused a significant reduction in [64Cu]Cu-DOTATATE uptake in the coronary arteries whereas this was not seen in the placebo treated group. In addition, [64Cu]Cu-DOTATATE PET/CT as a marker of coronary inflammation correlated with the systemic inflammation marker hs-CRP.